Local buckling on large sandwich panels used in light aviation: Experimental setup and failure scenarios. (15th January 2023) - Ginot, M.; Bouvet, C.; Castanié, B.; Serra, J.; Mahuet, N.
Abstract: The design of light aircraft sandwich structures is driven by a local buckling phenomenon named "wrinkling" which can be the primary cause of failure of such structures. Structural tests using the VERTEX methodology were performed to access the wrinkling behaviour of 558x536 mm 2 technological sandwich specimens representative of the design used in light aviation. The operating principle of the VERTEX machine is the use of four hydraulic actuators to load a rectangular box structure, the upper part of the central box being closed by the sandwich under test. Thus, sandwich specimens were tested under compressive and shear loading. A wrinkling scenario was identified thanks to Stereo Digital Image Correlation and a high-speed camera. Wrinkling localisation is driven by mechanical and geometrical aspects. Experiments on wrinkling in sandwich panels remain rare in the literature at this level of the test pyramid for certification of aeronautical structures. This upper scale presents some advantages as it allows multiaxial loading and boundary conditions consistent with a lightweight aeronautical structure. Technological elements can also be added to study their influence on the structure. The result will lead to interesting future investigations on the dialogue between experiments and models in a forthcoming paper.